(untitled) (Research, Society and Development, 2022)
Child development consists of the individual’s biological and behavioral transformations when faced with stimuli and experiences. The moment of playing, whether free or programmatic, allows the child to develop wide and/or fine movements, as well as the development of the sensory part. This study seeks to investigate the scientific evidence on the influence of playful stimulation when used in physical therapy approaches and the response to child development. This is an integrative literature review, using a sample of 7 articles selected from data collection using DeCS and MeSH descriptors: pediatrics/pediatrics/pediatrics; rehabilitation/ rehabilitation/ rehabilitation; therapeutic toy/ play therapy/ play therapy/ therapeutic play; motor skill/motor dexterity; toy/play; child development; ludic. With these definitions, searches were carried out in SciELO, PubMED, PEDro, ScienceDirect and Academic Google, including original national and international publications, in Portuguese, Spanish and English, in the period from 2010 to 2020. In the face of such research, play is a simple resource that allows the best interaction on the part of the child in therapy. The use of visual aids helps to improve mood and, depending on the way it is used, can limit or help in therapeutic approaches to the response of each child. In view of the evidence, playful stimuli have a great therapeutic potential and are capable of stimulating points that have been little explored by physiotherapy so far, seeking interaction and physiotherapeutic evolution from each limitation, with easy-to-adapt resources.